mHealth to Improve the Diet Among Low-Income Populations Enrolled in an Established U.S. Nutrition Program: Design and Rationale of a Randomized Controlled Trial - Heather Noel Fedesco; David A. Evans; David A. Evans; Nolan Kline; William Bart Collins; William Bart Collins; William Bart Collins (Frontiers Media S.A., 2015)
Aim: To describe the theoretical basis, and implementation of a randomized controlled trial to improve the diet and nutrition of low-income families in the United States. Background: Numerous community and state-wide programs exist in the United States to help improve the health and well-being of people with low incomes. One state-wide program, Small Steps to Health (Small Steps), focuses on improving diet and nutrition among SNAP (Supplemental Nutrition Assistance Program) recipients. Small Steps is a series of 10 1-hour educational classes that focus on a range of nutritional and diet topics, including: how to read food labels, how to prepare and cook home meals, as well as various ways to improve diet (e.g., reducing fat/sugar and increasing fruit/vegetable consumption). This program has been found to be effective in increasing vegetable consumption, meal planning, and physical activity. However, there has been no difference found in overall diet change nor in difficult diet behavior change, such as eliminating sugary drinks, reducing fast food intake, and replacing high-fat and sugar snacks with healthier options. Changing difficult behaviors requires more than education. For example, research shows that learning why sugary drinks are unhealthy is not enough to stop people from drinking these beverages. Beyond education, people benefit from counseling that focuses on increasing motivation and confidence, assistance with overcoming barriers, identifying social support, and creating specific action plans. Providing behavior change counseling to large numbers of people is challenging, however. Widespread use of short-message services (SMS) provides one potential tool for researchers to help individuals change difficult behaviors. For instance, SMS intervention is effective at helping smokers reduce or eliminate cigarettes, increase patients adherence to various medical regiments, and most importantly, aid in weight loss. Although promising, one of the limitations with current SMS interventions is that most have relied on providing reminder texts at the conclusion of an education/counseling session(s) − either reinforcing previous educational material or providing basic motivational messages. Very few have focused on incorporating effective counseling techniques to promote behavior change through interactions with participants during these educational sessions. The aim of our study is to explore what types of SMS behavior change techniques are most effective at helping individuals make challenging behavior change regarding diet and nutrition − Counseling vs. personalized Coaching vs. Reminding text messages. Method: To describe the design and rationale of an SMS randomized four-arm control trial that compares the dietary changes of an intervention using: 1) a standardized Counseling SMS group; 2) a personalized Coaching SMS group; 3) an educational information Reminding SMS group; each of which are compared to 4) the usual care control condition of a No SMS group. The Counseling and Coaching SMS groups were developed based on constructs of social cognitive theory (self-efficacy, motivation and outcome expectations) and the theory of planned behavior (barriers, social support, and action plans). Reminding SMS was the attention-control group and No SMS was the true control. A total of up to 300 SNAP recipients enrolled in the Small Steps to Health program in the state of Indiana will be randomized into one of four groups for three months to determine the efficacy of text-based behavioral interventions focusing on diet and nutrition. Every two weeks, participants will focus on a specific dietary behavior corresponding with the first four lessons taught in the Small Steps class. Behavior Change 1 (weeks 1 & 2): drink water instead of sugary beverages. Behavior Change 2 (weeks 3 & 4): eat breakfast every day. Behavior Change 3 (weeks 5 & 6): choose fruit as snacks and dessert instead of calorie-laden sweet and high-fat snack foods. Behavior Change 4 (weeks 7 & 8): switch to low-fat calcium sources. The main outcome measured is improvement in overall diet using a Self- 24-Hour Dietary Recall (ASA-24) and a Food Frequency Questionnaire (NHANES Food Questionnaire). Secondary outcomes are: specific behavior changes (as described above) as well as confidence, motivation and outcome expectation. Study completion is anticipated in May 2016. Conclusion: The results of this SMS intervention will inform the Small Steps program on the best way to incorporate technology into their program. In other words, does standardized counseling, personalized coaching or simple reminders work best for helping SNAP recipients improve their diets? If effective, the results will be implemented into the Small Steps To Health program.